2016
DOI: 10.5194/acp-16-9067-2016
|View full text |Cite
|
Sign up to set email alerts
|

Ice nucleating particles in the Saharan Air Layer

Abstract: Abstract. This study aims at quantifying the ice nucleation properties of desert dust in the Saharan Air Layer (SAL), the warm, dry and dust-laden layer that expands from North Africa to the Americas. By measuring close to the dust's emission source, before aging processes during the transatlantic advection potentially modify the dust properties, the study fills a gap between in situ measurements of dust ice nucleating particles (INPs) far away from the Sahara and laboratory studies of ground-collected soil. T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
142
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1
1

Relationship

5
5

Authors

Journals

citations
Cited by 105 publications
(166 citation statements)
references
References 81 publications
(122 reference statements)
20
142
4
Order By: Relevance
“…For conditions below water saturation, dust events yielding higher INP concentrations at the JFJ have been reported before (Chou et al, 2011) and in the Saharan air layer by aircraft sampling (DeMott et al, 2003b). At water-saturated conditions, this is the first study to clearly show that during a SDE at the JFJ an increase in INPs is observed at 242 K. This agrees with the findings of an increase in INP concentrations observed during minor influence of Saharan dust (Boose et al, 2016b). We note that at 265 K an increase in immersion INPs at the JFJ was not observed during SDEs , indicating that dust contributes to ice nucleation at colder temperatures as has been previously suggested in numerous studies (see references in Hoose and Möhler, 2012;Murray et al, 2012;Kanji et al, 2017).…”
Section: Case 6 February 2015: Sdesupporting
confidence: 81%
“…For conditions below water saturation, dust events yielding higher INP concentrations at the JFJ have been reported before (Chou et al, 2011) and in the Saharan air layer by aircraft sampling (DeMott et al, 2003b). At water-saturated conditions, this is the first study to clearly show that during a SDE at the JFJ an increase in INPs is observed at 242 K. This agrees with the findings of an increase in INP concentrations observed during minor influence of Saharan dust (Boose et al, 2016b). We note that at 265 K an increase in immersion INPs at the JFJ was not observed during SDEs , indicating that dust contributes to ice nucleation at colder temperatures as has been previously suggested in numerous studies (see references in Hoose and Möhler, 2012;Murray et al, 2012;Kanji et al, 2017).…”
Section: Case 6 February 2015: Sdesupporting
confidence: 81%
“…To quantify the initial stage of ice nucleation in the atmosphere, multiple sampling techniques are now being used in field studies (Hader et al, 2014;Mason et al, 2015;DeMott et al, 2015;Stopelli et al, 2015;Boose et al, 2016;Schrod et al, 2016Schrod et al, , 2017. Since these various measurements are being used as bases for developing numerical model parameterizations for different emission sources, their comparability should be assessed.…”
Section: Introductionmentioning
confidence: 99%
“…Continuous flow diffusion chambers (CFDCs) have provided a means to understand ice cloud formation by measuring INP concentrations in the field. By exposing an ambient aerosol population to controlled humidity and temperature conditions, the ability of natural aerosols to act as INPs can be quantified (DeMott et al, 2003a, b;Chou et al, 2011;Boose et al, 2016).…”
Section: Introductionmentioning
confidence: 99%